Immunogenicity and safety of HBAI20 Hepatitis B vaccine in non‐responders: Double‐blinded, randomised, controlled phase 2 trial. (24th May 2021) - Koc, Özgür M.; de Smedt, Philippe; Kremer, Cécile; Robaeys, Geert; van Damme, Pierre; Hens, Niel; Almeida, Jorge; Falkenberg, Frank; Savelkoul, Paul; Oude Lashof, Astrid; ,
Abstract: Background & Aims: Approximately 5%–10% of the general population respond inadequately to licensed recombinant hepatitis B vaccines. We assessed the immunogenicity and safety of a new HBAI20 vaccine, consisting of a new AI20 adjuvant (20‐µg recombinant human IL‐2 attached to 20‐µg aluminium hydroxide) in combination with HBVaxPro®‐10 µg. Methods: In a double‐blinded, randomised, controlled phase 2 trial, 18‐ to 59‐year‐old healthy non‐responders (titre <10 mIU/ml after three or more doses of hepatitis B vaccine) were assigned (3:1 ratio) to receive either HBAI20 vaccine or HBVaxPro®‐10 µg in a 0, 1 and 2‐month schedule. The primary outcome was seroprotection (titre ≥  10 mIU/ml) measured 1‐3 months following the third vaccination. Results: A total of 133 participants were randomised to receive either HBAI20 vaccine (n = 101) or HBVaxPro®‐10 µg (n = 32). In the modified intention‐to‐treat analysis, the seroprotection rate after the third vaccination was 92.0% (80/87) in the HBAI20 group and 79.3% (23/29) in the HBVaxPro®‐10‐µg group, P  = .068. Using a generalised linear mixed model to adjust for stratification factors, a higher odds of seroprotection with HBAI20 vaccine was shown (adjusted odds ratio = 3.48, P  = .028). Frequency of mild and moderate local adverse events was greater in the HBAI20 group than in the HBVaxPro®‐10 µg. Rates of severe local adverse events and systemic adverse events were low and similar in both groups. Conclusions: In this group of hepatitis B vaccine non‐responders, the HBAI20 vaccine demonstrated a higher seroprotection rate when adjusting for stratification factors and a similar safety profile compared to the licensed recombinant HBVaxPro®‐10 µg.